Pengendalian Kejahatan Korupsi dan Sustainable Development Goals di Indonesia - Rizky Bintang Setiawan; Mar'atus Sholikah; Rahmatika Azizi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
The pillars of SDGs 16 are Creating peaceful and inclusive societies for sustainable development, providing access to justice for all, and building effective, accountable, and inclusive institutions at all levels. Eradicating corruption is the key to the success of the other SDGs. This applies to countries where corruption is still high, including Indonesia. The purpose of this study is to see how much influence there is between corruption control and sustainable development and the strength of the relationship between the two variables so that it can become a reference for stakeholders in making decisions to achieve sustainable development goals in 2030. This study uses secondary data from the Worldwide Governance Indicators for 2002-2021 from the World Bank website. This type of research uses a quantitative approach. The study using objectives of this study, a simple linear regression analysis, was performed using the STATA17 statistical software application. The study's results found that the corruption crime control variable affected the SDGs in Indonesia and a strong positive correlation existed between these variables.